Independent prescribing in primary care: A survey of patients', prescribers' and colleagues' perceptions and experiences. (18th March 2019) - Hindi, Ali M. K.; Seston, Elizabeth M.; Bell, Dianne; Steinke, Douglas; Willis, Sarah; Schafheutle, Ellen I.
Abstract: Besides doctors and dentists, an increasing range of healthcare professionals, such as nurses, pharmacists and podiatrists, can become independent prescribers (IPs). As part of an evaluation for independent prescribing funded training, this study investigated views and experiences of IPs, their colleagues and patients about independent prescribing within primary care. Questionnaires capturing quantitative and qualitative data were developed for IPs, their colleagues and patients, informed by existing literature and validated instruments. IPs were identified following independent prescribing training funded by Health Education England Northwest in 2015–2017. Quantitative data were analysed using descriptive statistics and qualitative data were analysed thematically. Twenty‐four patients, 20 IPs and 26 colleagues responded to the questionnaires. Most patient respondents had a long‐term medical condition ( n  = 17) and had regular medicines prescribed ( n  = 21). IPs were nurses ( n  = 14), pharmacists ( n  = 4), one podiatrist ( n  = 1) and one was unknown. Half of the IPs were current prescribers ( n  = 10), the other half were still training (to become) IPs ( n  = 10). Colleague respondents were doctors and nurses ( n  = 15) other healthcare professionals ( n  = 8) and practice managers ( n  = 3). Both current IPs ( n  = 9) and colleague respondents ( n  = 25) (strongly) agreed that independent prescribing improved the quality of care provided for patients. Nearly all colleagues were supportive of independent prescribing and believed that they worked well with IPs ( n  = 25). Patients' perceptions and experiences of their consultations with the IP were mostly positive with the vast majority of respondents (strongly) agreeing that they were very satisfied with their visit to the IP ( n  = 23). Key barriers and enablers to independent prescribing were centred on IPs' knowledge, competence and organisational factors such as workload, effective teamwork and support from their colleagues. Findings from this study were mainly positive but indicate a need for policy strategies to tackle longstanding barriers to independent prescribing. However, a larger sample size is needed to confirm findings.